2019
DOI: 10.1007/s13300-019-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness and Safety of Vildagliptin Add-On to Metformin Versus Other Oral Dual Antidiabetes Agents in Patients with Type 2 Diabetes: The China Prospective Diabetes Study

Abstract: Introduction The efficacy and safety of vildagliptin alone or with metformin is well established by randomized trials, but it is unknown whether it can be extrapolated to the real-world setting in Chinese patients with type 2 diabetes mellitus (T2DM). This study aimed to assess the effectiveness and safety of vildagliptin add-on to metformin versus dual oral antidiabetes drug (OAD), non-vildagliptin combination therapies in real-world Chinese patients with T2DM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Pre-PSM baseline results from our study showed that in this real-life setting in China, compared to patients on VM, those on AM were older, had a lower BMI, a longer disease duration, and lower baseline HbA1c. These characteristics for patients on AM were in general agreement with those for patients on nonvildagliptin combination therapy in China [18] and are consistent with previous real-life data on acarbose use, with East Asian patients on acarbose reported to be older and less obese [22]. The distinct prescription pattern for VM versus that for other dual OAD, non-vildagliptin combination therapies (including AM) in China might be partially attributed to physician preference, which requires further research in the future.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Pre-PSM baseline results from our study showed that in this real-life setting in China, compared to patients on VM, those on AM were older, had a lower BMI, a longer disease duration, and lower baseline HbA1c. These characteristics for patients on AM were in general agreement with those for patients on nonvildagliptin combination therapy in China [18] and are consistent with previous real-life data on acarbose use, with East Asian patients on acarbose reported to be older and less obese [22]. The distinct prescription pattern for VM versus that for other dual OAD, non-vildagliptin combination therapies (including AM) in China might be partially attributed to physician preference, which requires further research in the future.…”
Section: Discussionsupporting
confidence: 86%
“…The composite primary endpoint was defined as glycemic control (hemoglobin A1c \ 7%) at 12 months and without any tolerability event, including hypoglycemia, weight gain C 3%, and gastrointestinal events leading to discontinuation of the treatment. CI Confidence interval, OR odds ratio combination [18]. Pre-PSM baseline results from our study showed that in this real-life setting in China, compared to patients on VM, those on AM were older, had a lower BMI, a longer disease duration, and lower baseline HbA1c.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation